People and development: Dovey, K & de Jong, T (1990) Developing people: A guide for educational, business and community organizations. Grahamstown: Institute for social and individual development in Africa. - Bless, Claire; Solomon, Vernon (PINS-Psychology in Society, 2026)
The development imperative facing South African society make this book, Developing people welcome for a range of people and organizations engaged 1n or contemplating development projects. It is written in an easy and accessible style and is designed to be a practical guide or development manual.